Reservation of transporting capacities of freight transport fleet due to the quantitative increase of fleet freight capacity - Ковцур, Катерина Григорівна (Eastern-European Journal of Enterprise Technologies, 2014)
The potential to improve the efficiency of delivery with minimal costs due to reservation of transporting capacities of freight transport fleet in the logistics retail chains is presented in the given paper. The minimum of reduced logistics costs, which consist of shipping cost and loses, associated with incomplete delivery of goods to the retail network, was selected as a criterion of effectiveness. The mathematical models of impact of delivery conditions (characterized by the features of the traffic area and demand for goods) and parameters of the technological delivery process and transporting capacities of freight transport reservation methods due to the quantitative increase of freight transport fleet onto reduced logistic costs were developed. According to the result of numerical experiment there were obtained the approximation models of technological parameters and reserve of fleet transporting capacities by various means. Using the presented dependencies will allow companies that deliver "small" formats to the retail trade network to reduce logistics costs.